KEBIASAAN SARAPAN DAN STATUS GIZI PEKERJA DI KOTA JAYAPURA - Elisabet Bre Boli; Oktliana Pasangka; Dwi Astuti (HUMAN CARE JOURNAL, 2023)
Breakfast plays an important role in supporting the availability of energy and nutrients every day, including for workers. The regularity and quality of breakfast can improve the nutritional status and work productivity of workers, as well as reduce morbidity rates. This study aims to analyze the relationship between breakfast habits and the nutritional status of workers in Jayapura City. This research is a descriptive correlational study with a cross sectional study design. The subjects in this study were workers who live in Jayapura City, 399 respondents selected using accidental sampling technique. Methods of data collection using interviews and anthropometric measurements. The research instruments were questionnaires and observation sheets. The results of the Spearman test showed that there was a relationship between breakfast habits and the nutritional status of workers in Jayapura (p-value = 0.030). Regular breakfast habits of workers are associated with good nutritional status. It is necessary to increase the knowledge of workers in getting used to breakfast to meet nutritional needsKeywords: Breakfast habit; Nutritional status; Workers